Development of Blended Learning-Based E-Module for Islamic Religious Education Learning: Pengembangan E-Module Berbasis Blended Learning Pada Pembelajaran Pendidikan Agama Islam - Sulaiman, Muhammad (Universitas Muhammadiyah Sidoarjo, 2024)
This research is a development study utilizing a mixed-methods design to create an e-module based on blended learning for tenth-grade students at SMA Muhammadiyah 1 Palembang for the 2022-2023 academic year. The ADDIE model was employed for the development process, which includes Analysis, Design, Development, Implementation, and Evaluation phases. The Analysis phase identified the need for a new learning module due to student disengagement with traditional Qur’an Hadith instruction and curriculum requirements. In the Design phase, a comprehensive e-module structure was developed, incorporating essential learning elements and aligned with curriculum standards. During the Development phase, the e-module was created using Flipbook Maker, allowing for an interactive digital format. The Implementation phase involved testing the module with a small group of students and subsequently with a larger class, receiving positive feedback. The Evaluation phase assessed the module’s effectiveness through pre- and post-tests, alongside expert and user feedback. Results indicated that the e-module significantly improved student engagement and understanding, with expert reviews and student surveys confirming its effectiveness and applicability. The e-module, available at https://online.flipbuilder.com/stafd/keag/, is deemed a valuable tool for both face-to-face and distance learning. Future research could expand testing to a broader audience and explore further design improvements.